An investigation of the low temperature properties of plain and reinforced concrete slabs. - Jain, Satyendra Kumar. (University of Ottawa (Canada), 1968)
The object of this investigation was to determine the behavior of plain and reinforced cement concrete with regard to temperature in the range from -100°F to +140°F. The effects of temperature, strength of concrete, percentage of steel, and arrangement of steel on the coefficient of thermal expansion were studied. Results at the age of 15 days and 30 days are not satisfactory partly due to experimental error. However, the results at the age of 84 days are very satisfactory. Below freezing point of water the coefficient of thermal expansion of plain concrete is 2.44 x 10-6 per degree F for w/c ratio 0.708 and 3.43 x 10-6 per degree F for w/c ratio 0.434. For reinforced concrete with 5.5% steel these values are 3.82 x 10 -6 per degree F for w/c ratio 0.708 and 4.68 x 10-6 per degree F for w/c ratio 0.434. Above freezing point of water the coefficient of thermal expansion of plain concrete is 3.14 x 10-6 per degree F for w/c ratio 0.708 and 4.03 x 10-6 per degree F for w/c ratio 0.434. For reinforced concrete with 5.5% steel these values are 4.49 x 10-6 per degree F for w/c ratio 0.708 and 5.37 x 10 -6 per degree F for w/c ratio 0.434.
Keywords: Engineering, Civil.